2021
DOI: 10.1371/journal.pone.0246653
|View full text |Cite
|
Sign up to set email alerts
|

Association of lower urinary tract symptoms and hip fracture in adults aged ≥ 50 years

Abstract: Aim Lower urinary tract symptoms (LUTS) result in morbidities; however, their association with the occurrence of hip fracture is relatively unknown in the context of Asian studies. The purpose of the study was to investigate this link with the hip fracture risk in Taiwanese men and women aged 50 years and above. Materials and methods From 2000 through 2012, a population-based retrospective cohort study was conducted; claims data of 18,976 patients diagnosed with LUTS (dysuria, urinary retention, incontinence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…LUTSs are prevalent in elderly men and women and are characterized by incomplete voiding, hesitancy, diminished stream, and storage indications such as urgency with incontinence, increased frequency, and nocturia. Significant morbidity and a potential increase in the risk of falls are observed [8,9]. Recent studies have shown that testosterone replacement therapy (TRT) can improve male LUTSs [10].…”
Section: Introductionmentioning
confidence: 99%
“…LUTSs are prevalent in elderly men and women and are characterized by incomplete voiding, hesitancy, diminished stream, and storage indications such as urgency with incontinence, increased frequency, and nocturia. Significant morbidity and a potential increase in the risk of falls are observed [8,9]. Recent studies have shown that testosterone replacement therapy (TRT) can improve male LUTSs [10].…”
Section: Introductionmentioning
confidence: 99%